2018
DOI: 10.29311/ndtps.v0i13.2767
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Measuring Attendance and Engagement

Abstract: In this paper, we argue that, where we measure student attendance, this creates an extrinsic motivator in the form of a reward for (apparent) engagement and can thus lead to undesirable behaviour and outcomes. We go on to consider a number of other mechanisms to assess or encourage student engagement – such as interactions with a learning environment – and whether these are more benign in their impact on student behaviour i.e. they encourage the desired impact as they are not considered threatening, unlike the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Regarding student attendance, as remarked in [34], monitoring only the indicator of student presence in a course with enforced attendance can lead to misleading errors, once students may attend but still not engage with the exposed content. However, once student presence is facultative in tutorial classes, this indicator may reproduce the students' choice to interact with their peers and instructors in class -thus representing a positive form of engagement.…”
Section: Data Monitoring and Analysismentioning
confidence: 99%
“…Regarding student attendance, as remarked in [34], monitoring only the indicator of student presence in a course with enforced attendance can lead to misleading errors, once students may attend but still not engage with the exposed content. However, once student presence is facultative in tutorial classes, this indicator may reproduce the students' choice to interact with their peers and instructors in class -thus representing a positive form of engagement.…”
Section: Data Monitoring and Analysismentioning
confidence: 99%
“…These inputs included lecture attendance, number of submissions, number of clicks, number of visits, number of lecture/assessment tasks downloads, number of posts in discussion forums and more. Grey et al conducted a study on measuring lab attendance and student engagement in computer science and reported that attendance has no significant impact on student engagement (Grey & Gordon, 2018). Hussain et al developed a predictive model using various machine learning algorithms with student log data, the highest education level attained, final results, and assessment scores, as inputs to predict low-engagement students, and the relationship between student engagement and course assessment scores.…”
Section: Indicators Of Student Engagementmentioning
confidence: 99%
“…One significant challenge of engagement is in identifying activities and evidence by which it can be measured, but which do not have undesired effects themselves An example of an undesired effect is where students respond to measures such as attendance monitoring or monitoring of opening a resource, when the students know they are being observed and may behave in an affected manner e.g. to simply register then leave an event, or to open then immediately close a resource [5].…”
Section: Engagementmentioning
confidence: 99%